Rescinding incardination: Canon 125 - Huels, John M. (CLSA advisory opinions, 2001-2005, 2002)
A priest was incardinated in our diocese from a foreign country, but crucial information about this priest was withheld. If the bishop had known this information, he would not have incardinated this priest. Can his incardination be rescinded by decree of the bishop? If not, can the bishop take hierarchical recourse to the Holy See to have the incardination nullified?